Strategi Pengelolaan Sampah Berbasis Komunitas dalam Mewujudkan Lingkungan Bersih dan Sehat (Studi Kasus Moluccas Coastal Care) - Merel Maruwemay; Mohammad Amin Lasaiba; Edward Gland Tetelepta (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Waste issues in the coastal area of Ambon City present a serious challenge that affects both the environment and public health. This study aims to identify and analyze community-based waste management strategies implemented by Moluccas Coastal Care (MCC) to achieve a clean and healthy environment. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, questionnaires, and documentation. The results show that MCC implements the 4R strategy (Reduce, Reuse, Recycle, Replace) through education, campaigns, and practical actions such as clean-up events and recycling workshops. This strategy has succeeded in increasing public awareness, although challenges remain regarding low participation, limited facilities, and insufficient policy support. In conclusion, community-based waste management effectively drives behavioral change and maintains the coastal environment, but broader collaboration is needed for long-term sustainability.